Intake of high-purity insoluble dietary fiber from Okara for the amelioration of colonic environment disturbance caused by acute ulcerative colitis. Issue 1 (9th December 2021) - Lyu, Bo; Wang, Yi; Fu, Hongling; Li, Jiaxin; Yang, Xiaoqing; Shen, Yue; Swallah, Mohammed Sharif; Yu, Ziyue; Li, Yang; Wang, Huan; Yu, Hansong; Jiang, Lianzhou
Abstract : High-purity insoluble dietary fiber from okara (okara-HPIDF) is a raw material with a potentially positive effect on colon health. Abstract : High-purity insoluble dietary fiber from okara (okara-HPIDF) is a raw material with a potentially positive effect on colon health. However, the mechanisms of the effect are far from clear. In this study, okara-HPIDF and low-purity dietary fiber from okara (okara-LPDF) were fed to C57BL/6 mice with acute ulcerative colitis induced by DSS. The levels of inflammatory factors, bacterial 16S rDNA sequencing, short-chain fatty acids (SCFAs), and bioinformatics were analyzed with the colonic tissue status. The results showed that the intake of HPIDF affected the proliferation of the key bacteria Shigella, Lactobacillus, and Peptostreptococcaceae in the PWY-2941 pathway and AEROBACTINSYN-PWY pathway, and then affected the synthesis of SCFAs, providing a positive role for colon health. However, the intake of HPIDF was unable to repair colonic injury caused by DSS-induced acute ulcerative colitis mainly owing to the abundance of Shigella in the colon. This study demonstrates that the recommended intake content of HPIDF can ameliorate colonic environment disturbance caused by acute ulcerative colitis, but not enough to relieve it.